Tumor-associated MerTK promotes a pro-inflammatory microenvironment and enhances immune checkpoint inhibitor response in triple-negative breast cancer - Crossman, Bridget E.; Harmon, Regan L.; Iida, Mari; Adams, Jillian M.; Lin, Candie Y.; Glitchev, Christine E.; Juang, Terry D.; Kerr, Sheena C.; Alexandridis, Roxana A.; Hyun, Meredith; Yang, David T.; Kang, Irene; et al. (Frontiers in Oncology, 2025)
IntroductionTriple-negative breast cancer (TNBC) is an aggressive subtype of breast cancer with no targeted treatment modalities. Currently, combination chemotherapy and immune checkpoint inhibitor (ICI) therapy are options for many TNBC patients; however, their efficacy is limited. Understanding what makes TNBCs responsive to immune therapy is crucial for improving patient outcomes.MethodsWe investigated the role of MerTK expression in TNBC using syngeneic and immunodeficient mouse models, human and murine cells lines, and human clinical samples. Flow cytometry, immunohistochemistry, RNA, multiplex ELISA, immunohistochemistry and multiplex immunofluorescence analysis were used to probe the effects of MerTK expression on the tumor immune microenvironment.ResultsOverexpression of MerTK in TNBC syngeneic mouse models leads to a marked delay in tumor growth, coupled with significant increases in anti-tumor M1 macrophage, CD4+ T cell, active CD8+ T cell, active NK cell, and NKT cell populations. This increase in pro-inflammatory cells contrasted with decreased anti-inflammatory polymorphonuclear myeloid-derived suppressor cells (PMN-MDSCs) and regulatory T cells (Tregs) in the TIME. In addition, tumors overexpressing MerTK exhibited very high sensitivity to both aPDL1 and aCTLA4 therapies, leading to durable tumor control and, in some cases, complete tumor regression without recurrence. Further, using Vectra multispectral analysis, elevated MerTK expression in human clinical samples was associated with increased levels of pro-inflammatory immune cells. In vivo and human clinical data suggest that tumor-bound MerTK expression is independent of PD-L1 expression in TNBC.ConclusionThese preclinical findings indicate that MerTK could serve as an independent predictive biomarker for ICI response in TNBC, potentially expanding the cohort of late-stage TNBC patients eligible for ICI therapy while reducing toxicity in early-stage patients by treating only those predicted to respond.